Sphingosine-1-phosphate hinders the osteogenic differentiation of dental pulp stem cells in association with AKT signaling pathways - Bongkun Choi; Ji-Eun Kim; Si-On Park; Eun-Young Kim; Soyoon Oh; Hyuksu Choi; Dohee Yoon; Hyo-Jin Min; Hyung-Ryong Kim; Eun-Ju Chang (International Journal of Oral Science, 2022)
Abstract Sphingosine-1-phosphate (S1P) is an important lipid mediator that regulates a diverse range of intracellular cell signaling pathways that are relevant to tissue engineering and regenerative medicine. However, the precise function of S1P in dental pulp stem cells (DPSCs) and its osteogenic differentiation remains unclear. We here investigated the function of S1P/S1P receptor (S1PR)-mediated cellular signaling in the osteogenic differentiation of DPSCs and clarified the fundamental signaling pathway. Our results showed that S1P-treated DPSCs exhibited a low rate of differentiation toward the osteogenic phenotype in association with a marked reduction in osteogenesis-related gene expression and AKT activation. Of note, both S1PR1/S1PR3 and S1PR2 agonists significantly downregulated the expression of osteogenic genes and suppressed AKT activation, resulting in an attenuated osteogenic capacity of DPSCs. Most importantly, an AKT activator completely abrogated the S1P-mediated downregulation of osteoblastic markers and partially prevented S1P-mediated attenuation effects during osteogenesis. Intriguingly, the pro-inflammatory TNF-α cytokine promoted the infiltration of macrophages toward DPSCs and induced S1P production in both DPSCs and macrophages. Our findings indicate that the elevation of S1P under inflammatory conditions suppresses the osteogenic capacity of the DPSCs responsible for regenerative endodontics.